Exploring the calming potential of peppermint: anxiolytic effects of mentha piperita essential oil on state and trait anxiety - Alvarado-García, Paul Alan Arkin (2024)
This study aimed to evaluate the anxiolytic effect of Mentha piperita essential oil on state and trait anxiety. Methods: The essential oil was extracted by hydrodistillation, and its chemical composition was analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). A total of 93 participants were divided into a control group (CG) and an experimental group (EG), with 47 participants in the EG receiving MPEO aromatherapy and 46 in the CG. Anxiety levels were measured using the State-Trait Anxiety Inventory (STAI) at pretest and posttest phases. Results: GC-MS analysis showed that menthol had the highest concentration (42.56%), followed by menthone (19.24%) and linalool (11.68%). Mixed model analysis revealed that group assignment (EG vs. CG) was a significant predictor of posttest state anxiety (F=16.508, p=0.001) and trait anxiety (F=9.091, p=0.003), independent of pretest scores, supporting the intervention’s effect on reducing anxiety. Posttest results showed a significant reduction in state anxiety in the EG compared to the CG (p=0.001) with a large effect size (r=0.508), while trait anxiety showed a moderate reduction (p=0.001, r=0.342). Conclusion: These findings suggest that Mentha piperita essential oil may effectively reduce state and trait anxiety, with a more pronounced impact on state anxiety.